Preparation and characterization of Nanostructured Porous Ternary and Quaternary Ill-Nitrides Alloys. - Hassan, Zainuriah (Universiti Sains Malaysia, 2016)

(untitled)
Nanostructured porous binary, ternary and quaternary Ill-nitrides (lnGaN and lnAIGaN) have been successfully fabricated using low cost ultraviolet (UV)-assisted photo-electrochemical (PEC) etching routes. Direct current (DC) has been employed to provide additional driving force to accelerate the PEC etching process, in which an improvement in optical characteristics of the semiconductors with regards to photoluminescence intensity and a stress relaxation in optical phonon modes has been attained through the formation of nanostructures/pores on the semiconductor surface.